Risk assessment in pulmonary arterial hypertension. (December 2016) - Raina, Amresh; Humbert, Marc
Regular patient assessment is essential for the management of chronic diseases, such as pulmonary arterial hypertension (PAH). Comprehensive patient assessment and risk stratification in PAH are important to guide treatment decisions and to monitor disease progression as well as patients' response to treatment. Approaches for assessing risk in PAH patients include the use of risk variables, as recommended in the 2015 European Society of Cardiology (ESC)/European Respiratory Society (ERS) pulmonary hypertension (PH) guidelines, and the application of risk equations and scores, such as the French registry risk equation and the REVEAL registry risk score. Risk stratification and risk scores are both useful predictors of survival on a population basis, and provide an estimate for individual patients' risk. The 2015 ESC/ERS PH guidelines recommend regular assessment of multiple variables at an expert centre. The respective merits and limitations of different risk assessment methods in PAH are discussed in this article, as well as some considerations that can be taken into account in the future development of risk assessment tools. Regular risk assessment with multiple parameters evaluates PAH disease progression and treatment response http://ow.ly/Nq0I305kgpU